Advanced Polymeric Nanoagents for Oral Cancer Theranostics: A Mini Review - Zhang, Guan-Meng; Nie, Shao-Chen; Xu, Zhao-Yuan; Fan, Ya-Ru; Jiao, Mai-Ning; Miao, He-Jing; Liang, Su-Xia; Yan, Ying-Bin (Frontiers in Chemistry, 2022)
Oral cancer is one of the most common tumours in the world threatening human life and health. The 5-year survival rate of patients with oral cancer has not been improved significantly for many years. The existing clinical diagnostic methods rarely achieve early diagnosis due to deficiencies such as lack of sensitivity. Most of the patients have progressed to the advanced stages when oral cancer is detected. Unfortunately, the traditional treatment methods are usually ineffective at this stage. Therefore, there is an urgent need for more effective and precise techniques for early diagnosis and effective treatment of oral cancer. In recent decades, nanomedicine has been a novel diagnostic and therapeutic platform for various diseases, especially cancer. The synthesis and application of various nanoagents have emerged at the right moment. Among them, polymer nanoagents have unique advantages, such as good stability, high biosafety and high drug loading, showing great potential in the early accurate diagnosis and treatment of tumours. In this review, we focus on the application of advanced polymeric nanoagents in both the diagnosis and treatment of oral cancer. Then, the future therapy strategies and trends for polymeric nanoagents applied to oral cancer are discussed, with the hope that more advanced nanomedical technology will be applied to oral cancer research and promote the development of stomatology.